Coparenting Profiles in the Context of Mexican-Origin Teen Pregnancy: Links to Mother-Daughter Relationship Quality and Adjustment - Perez-Brena, Norma J. (Fam Process, 2014)
The current study explored the multifaceted nature of the mother-adolescent coparental relationship with data from 167 Mexican-origin adolescent mothers and their own mothers at ten months post-childbirth. Profiles of mother-adolescent coparenting were created with latent profile analysis using adolescents’ reports of three dimensions of coparenting (communication, involvement and conflict). Four profiles were identified: (a) Harmonious Coparents (equal involvement, high communication, low conflict); (b) Harmonious-Adolescent Primary (adolescent is more involved than mother, high communication, low conflict); (c) Conflictual Coparents (equal involvement, high communication, high conflict); and (d) Conflictual-Adolescent Primary (adolescent is more involved than mother, moderate communication, high conflict). Families characterized by high mother-daughter conflict and psychological control prior to childbirth were more likely to belong in the Conflictual Coparents profile. In addition, adolescents’ and mothers’ depressive symptoms and parenting efficacy after childbirth were linked to profile membership, such that the Harmonious-Adolescent Primary profile reported the most positive adjustment patterns, whereas profiles with high coparental conflict (i.e., Conflictual Coparenting and Conflictual-Adolescent Primary profiles) showed the least positive adjustment patterns. Discussion considers the applied implications of identifying precursors to healthy and problematic mother-daughter coparenting for families of adolescent mothers in the early years of parenting.